2006
DOI: 10.1097/00024665-200611000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Nursing Records Into the NIC and the ICNP in a Korean Oriental-Medicine Hospital

Abstract: This study uses mapping methodology to examine the applicability of the Nursing Interventions Classification and the International Classification of Nursing Practice to nursing practice in a Korean Oriental-medicine hospital. Data were collected from the nursing records of 56 stroke patients in one unit, and intervention statements were mapped into NIC and ICNP. Of 147 unique nursing intervention statements extracted, 136 (92.52%) could be mapped into NIC and 99 (67.35%) statements could be completely mapped i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…Consistent with earlier work done to evaluate the concept coverage of the ICNP, 22,32,[37][38][39] less than half of the key assessment concepts had exact matches in the ICNP. Although many of the higher-level assessment concepts were found in the ICNP, the more detailed, descriptive concepts needed to represent patient assessment states at a more granular level (e.g., color, wound bed appearance, characteristics of wound drainage and pain descriptors) were not found in the ICNP.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with earlier work done to evaluate the concept coverage of the ICNP, 22,32,[37][38][39] less than half of the key assessment concepts had exact matches in the ICNP. Although many of the higher-level assessment concepts were found in the ICNP, the more detailed, descriptive concepts needed to represent patient assessment states at a more granular level (e.g., color, wound bed appearance, characteristics of wound drainage and pain descriptors) were not found in the ICNP.…”
Section: Discussionsupporting
confidence: 79%
“…Although other phases of the nursing process are supported by a large body of work, 5,6,30 -32 relatively few nursing terminology resources exist for representing data and information relative to assessment, despite the fact that data captured during assessment provides the foundation for all other phases in the nursing process. 15,16 Building on earlier work with the ICNP, [11][12][13][32][33][34][35][36] in this study we evaluated the adequacy of the ICNP as a representational model for nursing assessment documentation. We found that, with extensions to existing semantic relations and key concepts, the ICNP provides the formal structure and defines the properties needed to represent the PHS NAD model and to support electronic nursing assessment documentation.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this study, 19.63% of nursing statements were completely mapped to the ICNP. Conversely, 80.37% of 'incomplete mapping,' including mapping with higher level concepts, or with concepts from other axes, was higher than in previous studies [12][13][14]. The low rate of mapping may have been caused by both, the granularity problem, and the lack of proper concepts in home care nursing, in regards to ICNP terminology.…”
Section: Comparison Of Icnp Mapping Results With Other Studiesmentioning
confidence: 66%
“…These include: tracheal tube, pad, IV set, etc. Also, there are still missing concepts which were mentioned in previous studies, such as, I/O (input/output), smoking cessation, ulcer prevention, and daily living [14].…”
Section: Lack Of Concepts For Home Care Nursingmentioning
confidence: 99%
“…Several earlier studies have supported these findings. One study found that SNLs are needed to accurately reflect the contents of nursing practice in different cultures (Lee, Lee, & Jung, ). Lee, Yeh, and Ho () found that SNLs reduce individualization in patient documentation.…”
Section: Discussionmentioning
confidence: 99%